Analisis Shift Share dan Pengaruhnya Terhadap Pertumbuhan Ekonomi di Kabupaten Lombok Timur Tahun 2018-2023 - Wardana, Budi; Sahri, Sahri; Hidayat, Ali Akbar (Economic Reviews Journal, 2026)
This study aims to analyze the economic growth dynamics of East Lombok Regency during the period 2018–2023 using the Shift-Share method. This analytical approach decomposes economic growth into three main components—Regional Share (RS), Proportional Share (PS), and Differential Shift (DS)—to examine structural changes and sectoral performance within the regional economy. This quantitative research relies on secondary data obtained from the Central Statistics Agency (BPS), including Gross Regional Domestic Product (GRDP) data by industrial sector at both regional and provincial levels. The results show that the RS value of East Lombok is positive at Rp 2,067.28 billion, indicating that the region’s economic growth has generally matched or exceeded the average growth of West Nusa Tenggara Province. The PS value is also positive at Rp 310.20 billion, suggesting that East Lombok’s economic structure is relatively adaptive and supported by sectors growing faster than their provincial counterparts. However, the DS value is negative at –Rp 335.39 billion, reflecting weak overall sectoral competitiveness, although certain sectors—such as health services and public administration—exhibit competitive advantages. Overall, the findings indicate that East Lombok’s economic growth is primarily driven by external factors and structural composition, while internal competitiveness must be strengthened to ensure sustainable regional development.